2014
DOI: 10.1038/npp.2014.318
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory-Related Neural Activity Predicts Future Smoking Relapse

Abstract: Brief abstinence from smoking impairs cognition, particularly executive function, and this has a role in relapse to smoking. This study examined whether working memory-related brain activity predicts subsequent smoking relapse above and beyond standard clinical and behavioral measures. Eighty treatment-seeking smokers completed two functional magnetic resonance imaging sessions (smoking satiety vs 24 h abstinence challenge) during performance of a visual N-back task. Brief counseling and a short-term quit atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 73 publications
6
70
0
Order By: Relevance
“…Specifically, genes for nAChRs (and related proteins), determinants of nicotine metabolism, and brain imaging findings related to cigarette cue responses and nAChR levels have been found to predict response. Furthermore, several of these studies found that specific biomarkers may provide additional information for predicting response beyond subjective symptom or rating scale measures [137, 139, 144, 147]. Current research is focusing on clinical applicability of NMR [134], which is likely the most robust biomarker of treatment response found to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, genes for nAChRs (and related proteins), determinants of nicotine metabolism, and brain imaging findings related to cigarette cue responses and nAChR levels have been found to predict response. Furthermore, several of these studies found that specific biomarkers may provide additional information for predicting response beyond subjective symptom or rating scale measures [137, 139, 144, 147]. Current research is focusing on clinical applicability of NMR [134], which is likely the most robust biomarker of treatment response found to date.…”
Section: Discussionmentioning
confidence: 99%
“…In both of the preceding studies, increased activity in the insula during a cognitive control task predicted an improved likelihood of quitting. For the third study [144], smokers underwent fMRI (in abstinence and satiety) during which they performed the n-back working memory task. These sessions were followed by brief counseling and an abstinence attempt for 1 week.…”
Section: Brain Imaging Biomarkersmentioning
confidence: 99%
“…Moreover, systemic galantamine administration improves cognitive performance in rodents and humans during nicotine withdrawal [113, 114]. Given that cognitive deficits during nicotine withdrawal predict smoking relapse [115, 116], these results suggest that AChEIs may improve cognitive performance in abstinent smokers and prevent smoking relapse. Taken together, these studies suggest that AChEIs could be re-purposed as pharmacotherapies for smoking cessation [117].…”
Section: Neurotransmitter Mechanisms Regulating Nicotine Seekingmentioning
confidence: 99%
“…While these clinical predictor studies are helpful in guiding basic aspects of smoking cessation treatment, only recently have studies begun to emerge that demonstrate associations between brain function and smoking cessation treatment response. In this issue of Neuropsychopharmacology, Loughead et al, (2015) report an examination of whether functional magnetic resonance imaging (fMRI) measurements of working memory (WM)-related brain activity could be used to predict smoking relapse above and beyond clinical measures following a brief smoking cessation intervention. Study results link abstinence-induced decreases in left dorsolateral prefrontal cortical (DLPFC) activation and reduced suppression of posterior cingulate cortex (PCC) activity to treatment outcome, thereby implicating the executive control and default mode brain networks, respectively, to the ability to maintain abstinence.…”
mentioning
confidence: 99%